Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien pada Puskesmas Pakan Kamis Tilatang Kamang Kabupaten Agam - Siska, Adilla Juita (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
This study aims to determine the magnitude of Service Quality Impact on Patient Satisfaction of Pakan Kamis Public Health Center District Tilatang Kamang Agam.. The population in this study were patients using BPJS card whose Health Facility in Level I was registered at Pakan Kamis Public Health Center. In connection with the purpose of the above research, we hypothesized that "there is a significant influence partially and simultaneously between service quality which includes tangible, reliability, responsiveness, assurance, empathy, positive and significant impact on patient satisfaction at Pakan Kamis Public Health Center. The analysis used in this research is Binary Logistic Regression Analysis to know the effect of service quality to patient satisfaction hence obtained result that physical evidence (tangible) have positive effect 0,233 and not significant with value 0183, reliability (reliability) have positive effect 0,159 and not significant with a value of 0.042, responsiveness (positive responsiveness) of 0.283 and significant with the value of 0.016, assurance (assurance) has a positive effect of 0.311 and significant with the value 0.014, empathy (emphaty) has a positive effect of 0.103 and significant with the value 0.041.